Magnetic Resonance Spectroscopy with Longitudinal Multispin Orders - Velan, S. S.; Pichumani, Kumar; Murray, David; Raylman, Raymond R.; Scott, Tricia; Manivannan, Ayyakannu; Halliburton, Larry (Current Analytical Chemistry, 2008)
Longitudinal multispin orders can be created in spin systems that exhibit scalar, dipolar or quadrupolar couplings. They provide an effective way for measurement of scalar couplings and also to probe molecular interactions and dynamics. They cannot be separated by phase cycling or gradient selection methods which are the only known modes of separating different coherences. In this review we describe the frequency cycling procedure for separating various orders in weakly and strongly coupled spin systems. We provide the analytical solutions that permit determination of the frequency cycle for different spin systems. We also discuss the creation of longitudinal orders through relaxation. Finally we highlight the potential applications including spectral editing, measurement of relative signs of scalar couplings and structural properties of molecules.
Keywords: Scalar couplings